2011
DOI: 10.3386/w16758
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Fiscal Policy at the Zero Bound

Abstract: When the zero lower bound on nominal interest rates binds, monetary policy cannot provide appropriate stimulus. We show that in the standard New Keynesian model, tax policy can deliver such stimulus at no cost and in a time-consistent manner. There is no need to use inefficient policies such as wasteful public spending or future commitments to inflate. We conclude that in the New Keynesian model, the zero bound on nominal interest rates is not a relevant constraint on both fiscal and monetary policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
189
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(202 citation statements)
references
References 15 publications
10
189
0
3
Order By: Relevance
“…Figure 6 likewise shows that relative output and inflation also falls by more in the multiple currency case than in the single currency area. Finally, even under the optimal policy rule, the terms of trade still appreciates under the multiple currency case, while as before, the terms of trade in the single currency area depreciates 11 .…”
Section: Extension To Optimal Monetary Policymentioning
confidence: 99%
“…Figure 6 likewise shows that relative output and inflation also falls by more in the multiple currency case than in the single currency area. Finally, even under the optimal policy rule, the terms of trade still appreciates under the multiple currency case, while as before, the terms of trade in the single currency area depreciates 11 .…”
Section: Extension To Optimal Monetary Policymentioning
confidence: 99%
“…Correia, Farhi, Nicolini, and Teles (2013) analyzed the model in which the government can simultaneously choose all of labor-income tax, consumption tax, and lump-sum tax, and they showed that there is no role for government spending in that environment. Eggertsson and Woodford (2004) studied the optimal mix of a distortionary taxation and debt, assuming that the government spending is not available, and Eggertsson (2011) studied the effects of exogenous changes in distortionary taxes on allocations at the ZLB.…”
Section: Introductionmentioning
confidence: 99%
“…8 Neither of these studies however explores exact equivalence with a nominal devaluation, as we do in this paper. Lastly, this paper is similar in spirit to Correia, Farhi, Nicolini, and Teles (2011) who, building on the general implementation results of Correia, Nicolini, and Teles (2008), use fiscal instruments to replicate the effects of the optimal monetary policy when the zero-lower bound on nominal interest rate is binding.…”
Section: Introductionmentioning
confidence: 99%